IDENTIFIKASI LANDMARK ORBITAL CEPHALOMETRY MENGGUNAKAN METODE FUZZY C-MEANS CLUSTERING - Hasnawati Munandar; Ika Purwanti Ningrum; Jayanti Yusmah Sari (semanTIK, 2018)
Orthodontics is a branch of dentistry. In orthodontic treatment, several analyzes are needed, one of them is cephalometry analysis. Basically, cephalometry analysis is done manually, but this method requires a lot of time. In line with this, a computerized application is needed as a solution. In cephalometry analysis some landmarks are used as reference fields. Orbital is one of the landmarks that are difficult to identify. Orbital is located at the lowest point between the region of the eye cavity and the lower edge of the Orbital bone. One way to find Orbital landmarks is to segment the Orbital region. The segmentation aims to clearly separate the eye regions and Orbital bone in the cephalogram image. Fuzzy C-Means Clustering method is a segmentation method that can produce a clearer region partition. For this reason, the Fuzzy C-Means Clustering method is applied to get better segmentation results of the Orbital region so that the results of identification of the correct Orbital landmarks are obtained. Based on the results of testing on 90 image data provide an accuracy of 82.2% identification results with a cropping template size of 180 x 180 pixels.Keywords—Cephalometry Analysis, Fuzzy C-Means Clustering,  Landmark Cephalometry, Orbital